Privacy and data protection in India and Germany: A comparative analysis - Kim Arora (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2020)
This research report offers a comparative analysis of privacy and data protection in Germany and India. It compares the two regimes on four counts. First, it examines how the right to privacy and/or its allied rights have developed in the two countries historically. In this, it explores the political factors contributing to the understanding and acceptability of the principles of privacy in the decades after the Second World War. Second, it delves into the instruments and forms of state surveillance employed by both the countries and analyses how the presence of parliamentary and judicial oversight on intelligence agencies impacts individual privacy. In the third section, it compares how biometric identity systems have been deployed in the two countries, the safeguards designed around the same, and the legal challenges they have thrown up. Lastly, it evaluates data subject rights as defined under the General Data Protection Regulation (GDPR) together with the Bundesdatenschutzgesetz-Neu (BDSG-Neu) and how they compare with those as defined under the Draft Personal Data Protection Bill, 2018 in the Indian context.
Keywords: 300; data protection; surveillance; biometrics; Internet regulation; comparative analysis; India; Germany